2006
DOI: 10.1073/pnas.0603979103
|View full text |Cite
|
Sign up to set email alerts
|

Genome reduction inLeptospira borgpeterseniireflects limited transmission potential

Abstract: Leptospirosis is one of the most common zoonotic diseases in the world, resulting in high morbidity and mortality in humans and affecting global livestock production. Most infections are caused by either Leptospira borgpetersenii or Leptospira interrogans, bacteria that vary in their distribution in nature and rely on different modes of transmission. We report the complete genomic sequences of two strains of L. borgpetersenii serovar Hardjo that have distinct phenotypes and virulence. These two strains have ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
334
3
28

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(388 citation statements)
references
References 60 publications
(44 reference statements)
9
334
3
28
Order By: Relevance
“…It has already been reported that high-passage strains can present impaired virulence [40]. On the other hand, although uncommon, some strains may be virulent in host animals but not in the experimental model as is the case for serovar Hardjo subtype A strains [7]. The Skoll strain was isolated from an asymptomatic mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that high-passage strains can present impaired virulence [40]. On the other hand, although uncommon, some strains may be virulent in host animals but not in the experimental model as is the case for serovar Hardjo subtype A strains [7]. The Skoll strain was isolated from an asymptomatic mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequences are now available for Leptospira interrogans serovars Lai and Copenhageni and L. borgpetersenii serovar Hardjo [7][8][9]. Both China [9] and Brazil [8] have made research in leptospirosis a priority in order to address this emerging public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Since glycolysis does not exist in L. interrogans, it is not unusual that we detected few phosphosites in the proteins involved in carbohydrate metabolism. Another potential reason why fewer phosphosites were identified in L. interrogans may be due to the presence of more phosphatases in L. interrogans (25) compared to E. coli (5), which may lead to more frequent dephosphorylation in L. interrogans. In addition, the significantly overrepresented eukaryoticlike consensus sequences were not found in E. coli and B. subtilis.…”
Section: Comparison Of Ptm Patterns Of L Interrogans With Other Speciesmentioning
confidence: 99%
“…Despite advances in prevention and therapy, the molecular mechanisms of pathogenesis in leptospirosis remain almost completely unknown. The genome sequences of the pathogenic L. interrogans serovar Lai and serovar Copenhageni, the pathogenic L. borgpetersenii serovar Hardjo and the saprophytic L. biflexa serovar Patoc have been reported [3][4][5][6]. The accomplishment of these sequencing projects greatly facilitated the studies of Leptospira physiology and pathology at the genomic [4][5][6], transcriptomic [7,8] and proteomic levels [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, using primers specific for hbpA in the genome of serovar Lai, we identified all the serovars belonging to L. interrogans by PCR. While specific primers can now be designed from the increasingly available whole genome sequence data in order to identify other species (Bulach et al, 2006), PCR may not be economically viable as a routine diagnostic test and, because of the inherent problem of false positivity, cannot be used as the sole diagnostic test. HbpA IgG ELISA therefore offers considerable promise for the screening of both systemic leptospirosis and leptospiral uveitis.…”
Section: Discussionmentioning
confidence: 99%